2012
DOI: 10.1088/0960-1317/22/8/085016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fabrication and resonant optical coupling in various 2D micro-resonator structures in a UV210 polymer

Abstract: In this paper, we report on the design and the overall realization of micro-resonators based on the development of adequate processes on a UV210 polymer. These micro-optical structures are developed by deep ultraviolet lithography allowing fabrication of nano-structured devices by means of low cost and reproducible processes. Two families of resonant micro-structures shaped on disk and stadium with various sizes are investigated. Structural and optical imaging characterizations have been carried out to ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…It is well reported that this process has allowed resolutions <400nm in the size of the IO devices. The whole fabrication procedure and the full quality control of the photonic device is reported elsewhere [21,22]. The microresonator is based on a racetrack shape and light is laterally coupled with a straight tapered optical waveguide, Figure 1.…”
Section: Io Device Based On Polymeric Microresonatormentioning
confidence: 99%
“…It is well reported that this process has allowed resolutions <400nm in the size of the IO devices. The whole fabrication procedure and the full quality control of the photonic device is reported elsewhere [21,22]. The microresonator is based on a racetrack shape and light is laterally coupled with a straight tapered optical waveguide, Figure 1.…”
Section: Io Device Based On Polymeric Microresonatormentioning
confidence: 99%
“…Integrated polymeric micro-resonators are fabricated through deep UV (DUV) photolithography procedures and are based on UV210 photoresist [11][12] . This specific DUV-polymer is made of poly p-hydroxystyrene and poly t-butyl acrylate; it is called an amplified chemical photoresist including a photo acid generator so as to increase the sensitivity with energy exposure and to obtain a better photolithography mechanism.…”
Section: Polymer Materialsmentioning
confidence: 99%
“…This gap value overcomes those discussed in previous publications, where we also observed clear resonance transmission. 15,16 The R ¼ 50 mm radius and the Lc ¼ 60 mm coupling length are both main features characterizing the Figure 1 Schematic representation of racetrack microresonator. Parameters R, Lc and g represent, respectively, the radius, the coupling length and the distance between the rib waveguides and the microresonators geometry of a racetrack.…”
Section: Microracetrack Designmentioning
confidence: 99%
“…11,18 -20 In this work, we present the viability of a specific microresonator, based on a racetrack shape and on UV210 photoresist, as a temperature and glucose sensor. Recently, UV210 photoresist has been used as single mode rib waveguides 21 and submicrometer 2D-resonators 15 demonstrating the high capability of the polymer for photonic miniaturization. Then, the design and the overall fabrication and optical characterization of a cascade of multiple microresonators acting as modal filters have been presented.…”
Section: Introductionmentioning
confidence: 99%